Design and Application Prototype of soft starting Three-Phase AC Motor by Using Analog Electronics Control for Teaching Aids of Power Electronics Practice - Effendi, Effendi; Zakwansyah, Zakwansyah (LPPM Politeknik Aceh Selatan, 2024)
In general, palm oil processing factories, from fresh fruit bunches to Crude Palm Oil, require three-phase electric motors to drive or rotate it. The problems that often arise when using three-phase electric motors simultaneously in large numbers will result in very large surges in the electric current, which can affect the performance of electronic devices. To overcome this problem, a prototype of a three-phase AC voltage regulator circuit was made by adjusting the SCR triggering delay angle using an analog electronics equipment control that can be used for three-phase motor soft start applications in a palm oil factory. This prototype will be used as a learning tool for the practical for Aceh Polytechnic students for power electronics courses. This system is built with a method where the three-phase source is first lowered using a transformer arranged in a star on the primary and secondary sides, then each voltage is compared to the ground using an IC LM324, which aims to produce pulses wave. This pulse then connected to a triangular wave generator circuit, this triangular wave is then compared with the DC source voltage from the potentiometer, which aims to regulate the SCR triggering angle of SCR via MOC3063 driver, where the load used is resistive and connected in a star. The measurement using an oscilloscope and observing the change of triggering angle for several variations of each phase, the different Vrms voltage between measurements compared to mathematical analysis influenced by several factors, including, the transformer is made of three transformers that not identically, the electronic components used are not in ideal condition, and observations on the oscilloscope are carried out visually using the eye and manually adjusting the potentiometer rotation so that the level of measurement accuracy between one person and another will produce different values.